Censorship : policy and practice during the Second World War. - National Archives (Great Britain) (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2023)
Censorship: Practice and Policy during the Second World War explores British postal and telegraph censorship throughout a pivotal era of modern history. The collection contains 23,500 images drawn from Ministry of Defence files at The National Archives. It begins by surveying the first tentative steps that were taken, following the outbreak of conflict in 1939, to implement and to co-ordinate censorship. Documents reveal how hastily-assembled censorship teams looked back to the First World War for lessons and instructional precedents whilst adapting to the major technological developments that had occurred since. The work undertaken by censorship units - which necessitated keeping a close eye on all communications that could reveal sensitive or dangerous information to the enemy - soon became one of the most important, if somewhat underappreciated, fronts in the so-called "secret war".
Date range: 1939-1945.
Keywords: World War, 1939-1945 -- Censorship -- Great Britain; World War, 1939-1945 -- Communications; Censorship